Super stretchable electroactive elastomer formation driven by aniline trimer self-assembly - Chen, Jing (Chemistry of materials : a publication of the American Chemical Society, 2015)
Biomedical electroactive elastomers with a modulus similar to that of soft tissues are highly desirable for muscle, nerve, and other soft tissue replacement or regeneration, but have rarely been reported. In this work, superiorly stretchable electroactive polyurethane-urea elastomers were designed based on poly(lactide), poly(ethylene glycol), and aniline trimer (AT). A strain at break higher than 1600% and a modulus close to soft tissues was achieved from these copolymers. The mechanisms of super stretchability of the copolymer were systematically investigated. Crystallinity, chemical cross-linking, ionic cross-linking and hard domain formation were examined using differential scanning calorimetry (DSC), X-ray photoelectron spectroscopy (XPS), dynamic light scattering (DLS), nuclear magnetic resonance (NMR) measurements and transmission electron microscopy (TEM). The sphere-like hard domains self-assembled from AT segments were found to provide the crucial physical interactions needed for the novel super elastic material formation. These super stretchable copolymers were blended with conductive fillers such as polyaniline nanofibers and nanosized carbon black to achieve a high electric conductivity of 0.1 S/cm while maintaining an excellent stretchability and a modulus similar to that of soft tissues (lower than 10 MPa)